2010
DOI: 10.1063/1.3326943
|View full text |Cite
|
Sign up to set email alerts
|

Properties of TiO2-based transparent conducting oxide thin films on GaN(0001) surfaces

Abstract: Anatase Nb-doped TiO2 transparent conducting oxide has been formed on GaN(0001) surfaces using a sputtering method. Amorphous films deposited at room temperature were annealed at a substrate temperature of 500 °C in vacuum to form single-phase anatase films. Films with a thickness of 170 nm exhibited a resistivity of 8×10−4 Ω cm with absorptance less than 5% at a wavelength of 460 nm. Furthermore, the refractive index of the Nb-doped TiO2 was well matched to that of GaN. These findings indicate that Nb-doped T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…Kasai et al [111] reported anatase Nb-doped TiO 2 TCO formation on GaN(0001) surfaces using a sputtering method. Thin films of Nb-doped TiO 2 were deposited on an insulating GaN(0001) template using RF sputtering at substrate temperatures (T s ) ranging from RT to 400°C.…”
Section: Sputteringmentioning
confidence: 98%
See 2 more Smart Citations
“…Kasai et al [111] reported anatase Nb-doped TiO 2 TCO formation on GaN(0001) surfaces using a sputtering method. Thin films of Nb-doped TiO 2 were deposited on an insulating GaN(0001) template using RF sputtering at substrate temperatures (T s ) ranging from RT to 400°C.…”
Section: Sputteringmentioning
confidence: 98%
“…Transparent conducting TiO 2 films have been fabricated by various techniques [41][42][43][44][45][46]. These include both vacuumbased techniques (like sputtering, pulsed laser deposition-PLD, and chemical vapor deposition-CVD) and solutionbased techniques (like sol-gel, dip/spin-coating, and spray pyrolysis).…”
Section: Synthesis Of Tio 2 -Based Tsomentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the Sn doped In 2 O 3 (ITO) and F doped SnO 2 (FTO) are the most widely utilized n-type TCOs due to their excellent transparent conducting properties [5,6]. However, with the development of newly emerging optoelectronic devices, such as organic light emitting diodes (OLEDs), dye-sensitized solar cells (DSSCs), and GaN-based LEDs, it is still necessary to extend the material variety of TCOs [7] for the improvement of the performance of these devices [8].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition to the existing TCO materials such as Sn-doped In 2 O 3 ͑ITO͒ and Al-doped ZnO ͑ZnO:Al͒, rare metal-free anatase-phase Nbdoped TiO 2 ͑A-TiO 2 :Nb͒ has attracted attention since Furubayashi et al 3 discovered its transparent conducting property. 7 To utilize the transparent conducting property of A-TiO 2 : Nb in general use, forming anatase films on glass and amorphous/noncrystalline substrates by a cost-effective and practical deposition technique is preferred. They first obtained ͑001͒ A-TiO 2 : Nb epitaxial films exhibiting low resistivity ͑͒ and high transmittance ͑T͒ comparable with ITO ͑Ref.…”
Section: Introductionmentioning
confidence: 99%